PERAN MEDIASI EMOSI POSITIF TERHADAP IMPULSE BUYING PADA MATAHARI DEPARTEMENT STORE PONTIANAK - Pebrianti, Wenny; Ratnawati, Ratnawati (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2019)
The purpose of this study was to examine and analyze consumer responses to the Matahari department store in Pontianak on the effect of hedonic shopping value, store environment and positive emotion on impulse buying. The population in this study is the consumer of Matahari department store Pontianak, and the selected sample is consumers who have made impulsive purchases at Matahari department store Pontianak and there are as many as 97 samples. The results in this study indicate that there is a positive and significant effect between hedonic shopping value, and positive emotion on impulse buying. But the store environment has no significant effect on impulse buying